Pengaruh Sertifikasi Halal, Inovasi Ramah Lingkungan, dan Peer Influence terhadap Keputusan Pembelian Kosmetik Muslim Serang - Muhammad Rafi Putra Erdani; Moh. Mukhsin (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
Among Muslim consumers in Serang, the decision to purchase halal cosmetics is influenced by a combination of religious considerations, environmental awareness, and social surroundings rather than solely by personal beauty needs. This research investigates how mandatory halal certification, environmentally friendly product innovation, and peer influence contribute to consumer purchasing decisions. The study employed a quantitative approach using questionnaires distributed to 293 respondents chosen through purposive sampling techniques. Data analysis was conducted with IBM SPSS Statistics through multiple linear regression methods. The results reveal that all three independent variables significantly affect purchasing decisions for halal cosmetics. Among them, eco-friendly product innovation provides the greatest influence on consumer preferences, followed by peer influence and mandatory halal certification. In addition, the simultaneous testing demonstrates that the variables collectively have a meaningful impact on purchasing decisions. The coefficient of determination (R²) further indicates that the model possesses substantial explanatory capability in predicting variations in consumer behavior. Overall, the findings reflect that Muslim consumers in Serang tend to consider not only halal assurance in accordance with sharia principles, but also environmental responsibility and social acceptance when selecting cosmetic products.